Educaç\~ao no meio rural: Diferenciais entre o rural e o urbano - Caroline Nascimento Pereira; César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The present work presents an analysis of rural education compared to the urban education to support the formulation of educational policies for the rural areas. This area suffered for many years with the absence of specific educational policies, especially since the 1960s, when agricultural modernization took place in the countryside. Despite some policies implemented over the years, mainly in the 2000s, the differentials are still striking between the two realities. For the analysis of education in the area, the most recent data from the School Census, National Household Sample Survey (PNAD) and Demographic Census were used. The work begins with a discussion on development and educational public policies in rural areas, followed by a brief history of education in the Brazilian field. The following sections present socioeconomic information on the rural population, considering income and education, the profile of Brazilian basic education and the results of the Basic Education Assessment System (Saeb), with a focus on rural results.
Keywords: I21; P25; 330; rural development; public policies; rural education